Spectroscopy of Bs and Ds mesons - RYAN, SINEAD MARIE (Elsevier, 1998)
We study Bs and Ds spectroscopy in quenched lattice QCD using the Fermilab approach to heavy quarks. We obtain results at four lattice spacings, a, using O(a)-improved Wilson quarks. We compare and contrast the various methods for heavy quarks on the lattice, discussing discussing which methods work best for different physical systems and the ease with which calculations may be performed.
PUBLISHED
Keywords: Pure & Applied Mathematics